EXPLORASI PRAKTIK PROGRAM PENGENALAN PERSEKOLAHAN (PLP) DENGAN METODE EXPERENTIAL LEARNING DI MASA PANDEMI COVID-19 - Hartutik Hartutik; Yustinus Joko Yuniarto; Anselmus Joko Prayitno; Paulina Maria Ekasari Wahyuningrum; Hermania Bhoki; Jelahu Timotius Tote (Universitas Muria Kudus, 2023)
The purpose of this study is to describe the difficulties and the good steps that have been taken, reflect on their experiences, and plan follow-up difficulties. The research method used is descriptive qualitative. The research was carried out July-August 2021. Data collection techniques were interviews (4 supervisors, 2 supervisor teachers, and 5th semester students), documentation, and observation. Data analysis with data reduction techniques, data display, and verification and confirmation of conclusions. The research indicators are concrete experience, reflection and observation, abstract conceptual, and active experimentation.The results showed: 1) difficult experiences: internet facilities and networks, low student activity online, lack of confidence in students and also practitioners during the teaching and learning process, difficulty adjusting learning media according to class level, lack of content knowledge, difficulty linking material and examples in everyday life, as well as the selection of learning models. The good things that have been done are being able in terms of: communication, self-motivation, patience, and the courage to propose ideas to supervisors; 2) results of reflection: it is necessary to design learning tools, master the material, be creative and innovative, solve problems, and think positively about online learning; 3) Things that will be improved: being able to study independently (reading a lot of literature), designing creative media and applying methods that are problem solving in nature, and preparing teaching materials independently.